A Complication of BCG Vaccine: A Case of Localized Cutaneous Abscess due to Mycobacterium bovis - Nathalie Lussier; Anne-Marie Bourgault; Christiane Gaudreau; Pierre Turgeon (Canadian Journal of Infectious Diseases)
The attenuated bacille Calmette-Guérin (BCG) vaccine is administered to prevent tuberculosis. Complications of vaccination are uncommon. A case of cutaneous abscess due to BCG is presented in a 24-year-old woman. The abscess developed at the inoculation site four weeks after vaccination. Routine Gram stain and bacterial cultures of the pus were negative. The auramine stain was positive. Mycobacterial cultures were positive after 14 and 18 days, using the BACTEC 12B bottle and Löwenstein-Jensen media, respectively. The mycobacteria were identified as Mycobacterium bovis, vaccinal strain by high-performance liquid chromatography and DNA probe assays.